RETRACTED: The Nexus Between Vegetation, Urban Air Quality, and Public Health: An Empirical Study of Lahore - Khan, Muhammad Kaleem; Naeem, Kashif; Huo, Chunhui; Hussain, Zahid (Frontiers in Public Health, 2022)
Global climate change and the deteriorating quality of urban air are major issues affecting the atmospheric ecosystem of Pakistan. In poor monitoring and management of air pollution, improvements through the latest technologies such as GIS and remote sensing are required. This research involves spatial analysis, which discusses the impact of vegetation on air quality and public health. Data of air quality at twenty different points, showing the concentration of four pollutants, NOx, CO, SO2 and PM10, for 24 hours mean observations, are taken from EPA, Lahore. The results show that the concentration of SO2, CO and PM10 is exceptionally high at the site of Badshahi Mosque. The analysis shows that the highest polluted areas have the lowest vegetation levels, whereas less pollution concentration has more vegetation cover. Moreover, less vegetation has a higher household air pollution attributable death rate. The study suggests that greening strategies, vegetation screens and barriers should mitigate urban heat air pollution and minimize the air pollution attributed deaths. For pollution and vegetation monitoring, strict laws and monitoring programs must be implemented in major cities.